(untitled) (Communication & Society, 2007)
Direct participation of listeners in radio programmes is one of the most important elements, in radio strategies to get in touch with their audience. Today this strategy has been converted into a widely used professional practice in the western radio models. In the Spanish case, it is possible to make an historical study of its evolution up until the present moment, in which audience participation in the programmes has extended its technical potential and has increased its presence, as well as it hasdiversified its functions and contents. The present work describes the results of the content analysis made on the forms and techinques which the public channel of radio stations Radio 1, from Radio Nacional de España, adopted for direct participation of the audience in the radio programmes, during the 1999/2000 season. The conclusions outline the existings relations of content, purpose and the authority of audience contributions on the one hand, with the kind of programme, the broadcasting time and length, and the established professional mediation in each case, on the other.